ANALISIS DETERMINAN MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011â2014 - Rachma Indriyani, 12.05.52.0030; Puspitasari, Elen (Students Journal of Accounting and Banking, 2016)
This research aims to examine the influence of geographic diversification, audit tenure, audit firm size, institutional ownership, managerial ownership, firm size, leverage and profitability towards earnings management in manufacturingcompnies. Earnings management measured by discretionary accruals, which is counted using modified Jones model. This study uses documentary method from ICMD and annual reports of manufacture companies. Logistic regression technique is used for the data analysis.This study utilizes data from manufacturing companies listed at Bursa Efek Indonesia (BEI) in 2011 until 2014. The result of this study indicates audit tenure, audit firm size and profitability have significant influence in earnings management. Higher geographic diversification and institutional ownership might decrease earnings management. Meanwhile, geographic diversification, institutional ownership, managerial ownership, firm size,and leverage donât have significant influence to earnings management. is research aims to examine the influence of geographic diversification, audit tenure, audit firm size, institutional ownership, managerial ownership, firm size, leverage and profitability towards earnings management in manufacturingcompnies. Earnings management measured by discretionary accruals, which is counted using modified Jones model. This study uses documentary method from ICMD and annual reports of manufacture companies. Logistic regression technique is used for the data analysis.This study utilizes data from manufacturing companies listed at Bursa Efek Indonesia (BEI) in 2011 until 2014. The result of this study indicates audit tenure, audit firm size and profitability have significant influence in earnings management. Higher geographic diversification and institutional ownership might decrease earnings management. Meanwhile, geographic diversification, institutional ownership, managerial ownership, firm size,and leverage donât have significant influence to earnings management. Keywords: Earnings Management, Geographic Diversification, Audit Tenure, Audit Firm Size, Institutional Ownership, Managerial Ownership, Firm Size, Leverage, Profitability